Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2478/v10078-011-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Physical Performance Profiles of Elite Karate Kumite and Kata Competitors

Abstract: Karate tournaments consist of two equally important karate disciplines: the kumite and kata competitions. Due to being based both on the distinctive selection of movement techniques and their kinematic and kinetic patterns, we hypothesized that the elite kumite and kata competitors could differ regarding their anthropometric and physical performance profiles. Thirty-one senior male karate competitors of the national karate team (kumite n = 19; kata n = 12) participated in this study. The tests applied included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 31 publications
2
33
1
11
Order By: Relevance
“…Since the development of tournament competitions at national and international level, karate has gained growing popularity [1, 2] . Additionally, the first scientific article dealing with karate was published in 1966 [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of tournament competitions at national and international level, karate has gained growing popularity [1, 2] . Additionally, the first scientific article dealing with karate was published in 1966 [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Polish male karate athletes with similar general characteristics as our subjects ( (Gloc, Plewa, & Nowak, 2012). Koropanovski et al (2011) reported an analysis of anthropometrics and physical performance in 31 male karate competitors of the Serbian national karate team. The athletes were at similar age as our subject and had lower BMI compared to our results (24.55±2.1 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 97%
“…A great number of methods have been used in order to perform accurate evaluation and valid comparison analyzes of different anthropometric indices and body composition in martial arts practitioners (Pieter, Bercades, & Kim, 2006;Amusa & Onyewadume, 2001;Koropanovski et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to improvements in the anticipation reaction, the better the decision-making when the match. According to [5,10] "Reaction time has been considered as a key strategy in competitive sports the which require fast reactions such as karate," not just in kumite or kata. …”
Section: Introductionmentioning
confidence: 99%